Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1111/bph.12025
|View full text |Cite
|
Sign up to set email alerts
|

ARF6 and GASP‐1 are post‐endocytic sorting proteins selectively involved in the intracellular trafficking of dopamine D2 receptors mediated by GRK and PKC in transfected cells

Abstract: Background and Purpose GPCRs undergo both homologous and heterologous regulatory processes in which receptor phosphorylation plays a critical role. The protein kinases responsible for each pathway are well established; however, other molecular details that characterize each pathway remain unclear. In this study, the molecular mechanisms that determine the differences in the functional roles and intracellular trafficking between homologous and PKC‐mediated heterologous internalization pathways for the dopamine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 40 publications
0
21
0
Order By: Relevance
“…Knockdown of either GRK2 or arrestin3 significantly reduces the amount of agonist-induced D 2 receptor internalization (10,38), and overexpression of either protein enhances the amount of internalization seen in response to agonist (8,20,39,40). Furthermore, this response is potentiated when GRK2 and arrestin3 are overexpressed together (8,20,39).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Knockdown of either GRK2 or arrestin3 significantly reduces the amount of agonist-induced D 2 receptor internalization (10,38), and overexpression of either protein enhances the amount of internalization seen in response to agonist (8,20,39,40). Furthermore, this response is potentiated when GRK2 and arrestin3 are overexpressed together (8,20,39).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, this response is potentiated when GRK2 and arrestin3 are overexpressed together (8,20,39). Thus, it is possible that the reduced internalization of D 2 -A3 simply reflects its diminished GRK2 and arrestin3 recruitment, with a partial recruitment deficit somehow translating into a more severe internalization deficit.…”
Section: Discussionmentioning
confidence: 99%
“…ALIX directs receptors into budding intraluminal vesicles and couples YPX 3 L‐motif GPCRs to the ESCRT‐III complex. Similarly, lysosomal sorting of the DOR and the D2 dopamine receptor is mediated by the adaptor protein GASP‐1, which couples these proteins to the ESCRT‐0 complex independent of receptor ubiquitination. Recent findings have demonstrated that the DOR can recycle from the limiting membrane of the late endosome .…”
Section: Direct Ubiquitination Of Gpcrs and Endo‐lysosomal Sortingmentioning
confidence: 99%
“…T250A-PKCbII, Flagtagged T250A-PKCbII, K11/12R-b-arrestin2, and Flag-tagged K11/12R-b-arrestin2 were prepared by site-directed mutagenesis. The generation of PKCa, PKCbI, PKCbII, PKCe, and PKCf conjugated to GFP, along with PKCa, PKCbII, PKC c, and PKC d fused to HA has been described previously [20,21]. The shRNAs for GRK2, MDM2, and PKCbII were described previously [22][23][24].…”
Section: Plasmid Constructsmentioning
confidence: 99%